2019
DOI: 10.21037/atm.2019.08.62
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD2, CCL5 and CCR5 as potential therapeutic target genes for renal interstitial fibrosis

Abstract: Background: We aimed to explore potential gene biomarkers of renal interstitial fibrosis (RIF) due to a lack of effective and non-invasive methods for diagnosis.Methods: Three data sets (GSE22459, GSE76882 and GSE57731) including 350 samples were acquired from Gene Expression Omnibus (GEO) database. We used bioconductor limma package to perform background adjustment. Cluster analysis was conducted by 'edgeR' package to identify the differentially expressed genes (DEGs). We generated heat maps with using heatma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Thus, activation of STAT3 signaling upregulates DNMT1 expression and leads to DNA methylation (Zhang et al, 2006;Wang et al, 2017). Previous studies have demonstrated upregulation of CCL5 and STAT3 expression in kidney fibrosis, and their levels are positively associated with the degree of RIF (Bienaime et al, 2016;Pace et al, 2019;Zhang et al, 2019). Thus, CCL5/STAT3 signaling is involved in renal fibrotic diseases and is proposed to be a feasible therapeutic target for RIF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, activation of STAT3 signaling upregulates DNMT1 expression and leads to DNA methylation (Zhang et al, 2006;Wang et al, 2017). Previous studies have demonstrated upregulation of CCL5 and STAT3 expression in kidney fibrosis, and their levels are positively associated with the degree of RIF (Bienaime et al, 2016;Pace et al, 2019;Zhang et al, 2019). Thus, CCL5/STAT3 signaling is involved in renal fibrotic diseases and is proposed to be a feasible therapeutic target for RIF.…”
Section: Discussionmentioning
confidence: 99%
“…CCL5 is a major mediator and biomarker of inflammation and it recruits monocytes, macrophages, T cells, and eosinophils to the sites of injured kidneys. Indeed, a recent study showed that the CCL5 level was significantly associated with the intensity of RIF and CCL5 was identified as a potential intervention target for RIF ( Zhang et al, 2019 ). Our data from human CKD showed that the CCL5 level was elevated significantly, while the Klotho level was significantly decreased as eGFR declined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach allowed an improved understanding of the molecular mechanisms involved in cancer (21). Meanwhile, the heatmap package [version 1.0.12 (22)] was used to generate the heatmap of these DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study using the same GEO datasets screened CD2, CCL5, and CCR5 as potential therapeutic target genes in RIF by overlapping DEGs identified from GSE22459 and GSE76882 datasets and PPI network analysis (8). However, unlike the previous study, the candidate key genes of RIF in the present study were first identified by overlapping the RIF-related genes from WGCNA with DEGs from the two datasets.…”
Section: Discussionmentioning
confidence: 87%